2009
DOI: 10.1016/j.jpainsymman.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Assessment of Symptoms and Mobility in Palliative Care: Feasibility and Challenges

Abstract: The aims of the study were to explore the ability of cancer patients who are primarily receiving palliative care to use a touchscreen computer for assessment of symptoms and mobility and to investigate which factors predicted the need for assistance during the assessment. Before the main data collection, a pilot study was conducted to explore the preferences of these patients toward using such a computerized assessment tool. Patients were recruited from nine different inpatient and outpatient palliative care a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
3
24
1
Order By: Relevance
“…Furthermore, the respondents were not able to go to the next question until having completed the current one, thus avoiding missing responses. A concurrent feasibility study achieved a high completion rate and found no effect of gender or functional level on the rate of completion [35], and supported the use of computer-based questionnaires as feasible even in frail persons. Overall, cognitive function was not seriously affected in the sample.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, the respondents were not able to go to the next question until having completed the current one, thus avoiding missing responses. A concurrent feasibility study achieved a high completion rate and found no effect of gender or functional level on the rate of completion [35], and supported the use of computer-based questionnaires as feasible even in frail persons. Overall, cognitive function was not seriously affected in the sample.…”
Section: Discussionmentioning
confidence: 63%
“…Regarding physical function, we were able to differentiate between two patient categories, high and low KPS, that had different requirements for ergonomical adjustments for better interaction, e.g., in bed (low KPS) and at a table (high KPS). Other studies of similar patients have also suggested an impact of physical function when interacting with digital tools [13,16]. KPS provides an easy and unambiguous definition of the patients that are involved in the study, and we suggest the use of it to describe the informants.…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies designed to measure feasibility with qualitative methods, details of the users who have informed the study are unknown [14,34]. The methods used in healthcare studies are often quantitative, and causality of reduced interaction can be hard to prove statistically, especially if we do not know what to look for [13,21]. In technology development studies, qualitative data are often quite well described, but the important traits, from a medical point of view (and possibly also from an interaction point of view), of the informants are often missing [14,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the work of Fyllingen et al [18], Helbostad et al [19 ], and Pigott et al [20] is encouraging. These three research groups report on the development of tools for identifying patients' supportive care needs, including physical functioning and activities of daily living.…”
Section: Identifying Patients' Rehabilitation Needs At the End Of Lifementioning
confidence: 89%